(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
The primary function of a circuit breaker is to protect an electrical circuit from damage caused by overcurrent, short circuits, or overloads. It does this by automatically interrupting the flow of electricity when a fault is detected. Conventional mechanical circuit breakers (MCBs) can be too slow to ensure safety, as their mechanical time constant causes a delay in responding to faults like short circuits or overloads. This study aims to compare the performance of three types of circuit breakers including MCB, solid-state circuit breaker (SSCB), and hybrid circuit breaker (HCB) in two different conditions, namely residential and industrial applications. A simulation is carried out using ETAP 19 software, in which arc flash analysis is conducted to evaluate the performance of each circuit breaker. A Time-Current Curve (TCC) is analyzed to determine how quickly a circuit breaker can respond to a fault condition. This curve illustrates the relationship between the magnitude of current and the time it takes for the breaker to trip. By examining the TCC, it is possible to assess whether the circuit breaker provides adequate protection by clearing faults within acceptable safety limits, helping to prevent equipment damage and ensure system reliability. To ensure a comprehensive and reliable analysis, the simulation includes various models for each type of circuit breaker. These models differ in specifications, performance characteristics, and manufacturers, enabling for a more thorough evaluation of how each type performs under fault conditions and various operational scenarios. The result shows that HCBs outperform both MCBs and SSCBs in terms of fault clearing time across both residential and industrial applications.